MolDiscovery: learning mass spectrometry fragmentation of small molecules - Liu Cao (Nature Portfolio, 2021)
A large number of mass spectra from different samples have been collected, and to identify small molecules from these spectra, database searches are needed, which is challenging. Here, the authors report molDiscovery, a mass spectral database search method that uses an algorithm to generate mass spectrometry fragmentations and learns a probabilistic model to match small molecules with their mass spectra.